Comments on Ahmad, I.M. et al. Healthcare Workers Occupationally Exposed to Ionizing Radiation Exhibit Altered Levels of Inflammatory Cytokines and Redox Parameters. Antioxidants, 2019, 8, 12 - Joseph J. Bevelacqua; Seyed Mohammad Javad Mortazavi (MDPI AG, 2019)
This commentary is regarding the paper recently published by Ahmad et al [...]